2020
DOI: 10.1186/s12964-020-00621-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of carrageenan-induced cytokines production in macrophages

Abstract: Background Low molecular weight carrageenan (Cg) is a seaweed-derived sulfated polysaccharide widely used as inflammatory stimulus in preclinical studies. However, the molecular mechanisms of Cg-induced inflammation are not fully elucidated. The present study aimed to investigate the molecular basis involved in Cg-induced macrophages activation and cytokines production. Methods Primary culture of mouse peritoneal macrophages were stimulated with Kappa Cg. The supernatant and cell lysate were used for ELISA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 81 publications
3
21
0
1
Order By: Relevance
“…It has been reported that carrageenan toxicity is mediated by the TLR4-and NF-kB-associated pathways, NLRP3 inflammasome pathway, ROS-mediated damage and, hence, upregulation of pro-inflammatory cytokines [25,[29][30][31]. The role of pathways outlined above in immune cells is more pronounced compared with fibroblasts, which can be speculated to explain the difference in cytotoxic effects of semi-refined carrageenan on different types of cells.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that carrageenan toxicity is mediated by the TLR4-and NF-kB-associated pathways, NLRP3 inflammasome pathway, ROS-mediated damage and, hence, upregulation of pro-inflammatory cytokines [25,[29][30][31]. The role of pathways outlined above in immune cells is more pronounced compared with fibroblasts, which can be speculated to explain the difference in cytotoxic effects of semi-refined carrageenan on different types of cells.…”
Section: Discussionmentioning
confidence: 97%
“…Carrageenan is a sulfated polysaccharide substance used to produce inflammatory immune response in experimental animals leading to the release of pro-inflammatory mediators such as prostaglandin, histamine, bradykinin, leukotrienes, etc. [30]. The mechanism of carrageenan-induced inflammation in two-phase response, serotonin, and histamine released during the first phase followed by the release of prostaglandins, lysosome enzymes during the second phase [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response happens through the interaction of either pathogen-associated molecular patterns (PAMPs) or danger-associated molecular patterns with pattern recognition receptors [ 1 , 4 ]. For instance, engagement of PAMPs such as gram-negative bacteria-derived lipopolysaccharides (LPS) or carrageenan into toll-like receptor 4 will induce recruitment of adaptor proteins, MyD88 and TRIF, into the cytoplasm that eventually triggers inflammatory signaling cascades, including the activator protein-1 (AP-1) pathway [ 2 , 5 , 6 ]. The activation of the inflammatory signaling pathway is mediated by the initiation of signal transduction cascades activating a variety of intracellular signaling molecules.…”
Section: Introductionmentioning
confidence: 99%